1959
DOI: 10.1111/j.1476-5381.1959.tb00939.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Activity of a New Analogue of Oxytocin in Which the Tyrosyl Group Is Replaced by Phenylalanyl

Abstract: A new synthetic analogue of oxytocin with a phenylalanyl group instead of a tyrosyl group has been investigated. The most prominent biological properties of this peptide were its oxytocic activity on the rat or cat uterus in vivo and on milk-ejection pressure in the rabbit. Another remarkable feature was the striking difference in pressor activity measured in spinal cats and in anaesthetized rats. The presence of the phenylalanyl group in the molecule in the above-mentioned position did not increase the antidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1959
1959
1962
1962

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…These results offer some confirmatory evidence in man of the suggestion by Berde et al (1957) and Konzett & Berde (1959) …”
Section: Effects Of Oxytocin and Of Mixtures Of Oxytocin And Vasopressinsupporting
confidence: 75%
See 1 more Smart Citation
“…These results offer some confirmatory evidence in man of the suggestion by Berde et al (1957) and Konzett & Berde (1959) …”
Section: Effects Of Oxytocin and Of Mixtures Of Oxytocin And Vasopressinsupporting
confidence: 75%
“…1 c) called 'P-analogue 'by Berde, Doepfner & Konzett (1957), 'oxypressin' by Katsoyannis (1957) and here called phenylalanyl3-oxytocin according to the scheme of numbering the amino acids suggested by Konzett & Berde (1959), is of interest because it can be used to assess the relative importance of the amino acids in the 3-and 8-positions in the action of vasopressin on the kidney. It has been found by Berde et al (1957) to have an antidiuretic activity in the rat comparable to that of vasopressin, whereas substitution of the tyrosyl2 group of oxytocin by phenylalanine results in much 19-2 286 W. B. THOMSON less enhancement of the antidiuretic action (Konzett & Berde, 1959).…”
Section: Ne Uroh Ypophysial Hormones and The Kidney 285mentioning
confidence: 99%
“…Dieses Phänomen wurde auch bei der Reinigung anderer Oxy tocin-Analoga beobachtet (Konzett, 1959;Berde, Certetti und Konzett, 1959); es bedeutet, daß die biologische Eigenart eines neuen Peptids dieser Klasse bereits bei der pharmakologischen Prüfung des rohen synthetischen Präparates erkannt werden kann.…”
Section: Methodikunclassified
“…Both groups of workers found an oxytocic potency, measured on the isolated rat uterus, of 30 u./mg. On the other hand, Konzett & Berde (1959) reported that the milk-ejecting potency of the analogue prepared by Jaquenoud & Boissonnas was 140 u./mg. The corresponding analogue of vasopressin, phenylalanine2-lysine8-vasopressin, prepared by Boissonnas & Guttmann (1960) has a pressor potency equal to about one-fifth of that of the parent compound (Berde et al, 1961).…”
Section: Discussionmentioning
confidence: 99%